Three-dimensional numerical study of heat-affected zone in induction welding of tubes. Issue 1 (2nd January 2020) - Das, Prerana; Asperheim, John Inge; Grande, Bjørnar; Petzold, Thomas; Hömberg, Dietmar
Abstract : Purpose: Quality of the weld joint produced by high-frequency induction (HFI) welding of steel tubes is attributed to a number of process parameters. There are several important process parameters such as the speed of the welding line, the angle of the approaching strip edges, the physical configuration of the induction coil, impeder, formed steel strip and weld rolls with respect to each other, the pressure of the weld rolls and frequency of the high-frequency current in the induction coil. The purpose of this paper is to develop a 3D model of tube welding process that incorporates realistic material properties and movement of the strip. Design/methodology/approach: 3D numerical simulation by the finite element method (FEM) can be used to understand the influence of these process parameters. In this study, the authors have developed a quasi-steady model along with the coupling of electromagnetic and thermal model and incorporation of non-linear electromagnetic and thermal material properties. Findings: In this study, 3D FEM model has been established which gives results in accordance with previously published work on induction tube welding. The effect of the Vee-angle and frequency on the temperature profile created in the strip edge during the electromagnetic heating is studied. Practical implications: The authors are now able to simulate the induction tube welding process at a more reasonable computational cost enabling an analysis of the process. Originality/value: A 3D model has been developed for induction tube welding. A non-linearly coupled system of Maxwell's electromagnetic equation and the heat equation is implemented using the fixed point iteration method. The model also takes into account non-linear magnetic and thermal material properties. Adaptive remeshing is implemented to optimise mesh size for the electrical skin depth of induced current in the strip. The model also accounts for the high welding-line speeds which influence the mode of heat transfer in the strip.